Analysis of the Clinical Features of Intrauterine Ureaplasma urealyticum Infection in Preterm Infants: A Case-Control Study - Sun, Tong; Fu, Jianhua (Frontiers in Pediatrics, 2021)
Objective: To analyze the clinical characteristics of intrauterine Ureaplasma urealyticum (UU) infection in premature infants. Method: In this single-center retrospective case-control study, 291 preterm infants born in our hospital and hospitalized in our department and gestational age no more than 32 weeks, birth weight no more than 2000 g were included from January 2019 to January 2021. Lower respiratory tract secretion, gastric juice and urine were collected for UU RNA detection. The UU infection group included 86 preterm infants and the non-UU infection group included 205 preterm infants. We compared their clinical features, blood picture changes and disease outcomes using statistical analyses. Results: The clinical characteristics of premature infants such as the duration of oxygen use and ventilator use in hospital were significantly prolonged in the UU infection group (P<0.05). The levels of leukocytes, platelet and procalcitonin in the UU infection group were significantly higher than in the non-UU infection group (P<0.05). In terms of preterm complications, only the incidences of bronchopulmonary dysplasia, retinopathy of prematurity and metabolic bone disease in premature infants in the UU infection group were significantly higher than those in the non-UU infection group (P<0.05). The mode of delivery, maternal premature rupture of membranes, and postnatal leukocyte level were independent risk factors for UU infection, while gestational hypertension was a protective factor for UU infection. Conclusion: The level of leukocytes in postnatal blood images of premature infants could be used as a diagnostic index of UU infection, but the diagnostic efficiency was poor. High-risk neonates should undergo early screening of UU to prevent increase in preterm complications.